1999
DOI: 10.1152/jn.1999.81.2.781
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of LTP and LTD by Postsynaptic [Ca2+]i Elevation

Abstract: Long-term potentiation (LTP) and long-term depression (LTD), two prominent forms of synaptic plasticity at glutamatergic afferents to CA1 hippocampal pyramidal cells, are both triggered by the elevation of postsynaptic intracellular calcium concentration ([Ca2+]i). To understand how one signaling molecule can be responsible for triggering two opposing forms of synaptic modulation, different postsynaptic [Ca2+]i elevation patterns were generated by a new caged calcium compound nitrophenyl-ethylene glycol-bis(be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
375
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(398 citation statements)
references
References 34 publications
21
375
1
1
Order By: Relevance
“…Hill co-efficients and dissociation constants are set in line with previous experimental and theoretical studies, and the empirically observed competition between these two pathways is accounted for by dictating that kinase activity partially inhibits phosphotase activity [40,41,44,49,50]. Finally, the activation of kinase and phosphotase must also obey different kinetics, such that LTP can be induced rapidly, by a small number of triplet pairings, while significant LTD requires more sustained stimulation [15,17,29]. This is achieved by assigning a much more rapid time constant of decay to the kinase pathway compared to the phosphotase pathway (50ms and 2000ms respectively).…”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationmentioning
confidence: 71%
See 2 more Smart Citations
“…Hill co-efficients and dissociation constants are set in line with previous experimental and theoretical studies, and the empirically observed competition between these two pathways is accounted for by dictating that kinase activity partially inhibits phosphotase activity [40,41,44,49,50]. Finally, the activation of kinase and phosphotase must also obey different kinetics, such that LTP can be induced rapidly, by a small number of triplet pairings, while significant LTD requires more sustained stimulation [15,17,29]. This is achieved by assigning a much more rapid time constant of decay to the kinase pathway compared to the phosphotase pathway (50ms and 2000ms respectively).…”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationmentioning
confidence: 71%
“…Other experimental data indicates that potentiation and depression events are switch-like transitions between binary conductance states, mediated by kinase and phosphotase pathways that are co-activated and competitive [36][37][38][39][40]. The kinetics of kinase and phosphotase activation also differ significantly, as LTP can be rapidly induced by appropriate patterns of activity while LTD requires prolonged stimulation [15,17,29]. Computational modelling of synaptic plasticity has demonstrated that the dynamics of Calcium influx through the NMDA receptor (NMDAr) is sufficient to account for empirical data obtained using multiple stimulation protocols, integrating an array of experimental results within a single theoretical framework [18,[41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16,27,28) The spine can therefore be treated as a single compartment with respect to [Ca 2þ ] i under these conditions; ignoring gradients induced by the spatial localization of Ca 2þ pumps and exchangers on membrane surfaces. However, the spine cannot be considered a single calcium compartment for normal physiological stimuli.…”
Section: Ca 2þ In Dendritic Spinesmentioning
confidence: 99%
“…(17) Furthermore, genetic manipulation of the NMDAR subunit composition resulting in an increase in the amount of Ca 2þ entering the cell results in LTP induction at lower stimulation frequencies. (25) Fifth, direct manipulation of postsynaptic Ca 2þ levels using diffuse photolytic uncaging of chelated Ca 2þ is sufficient to induce both LTP and LTD. (16,(26)(27)(28) Specifically, large ($10 mM), brief ($3 sec) increases in [Ca 2þ ] i reliably induce LTP, whereas a modest ($0.7 mM), long ($60 sec) increases in [Ca 2þ ] i reliably induce LTD. (28) Spike-timing-dependent plasticity The temporal order of pre-and postsynaptic activation may also be important for the selective induction of LTP and LTD. (7,29) With the finding that an action potential, or spike, induced by a current injection into the soma, not only travels down the axon but also propagates back through the dendrites, (30) the timing of the presynaptic input (the release of glutamate) and the postsynaptic output (the spike) can be controlled with millisecond precision. A fascinating picture has since emerged.…”
Section: Introductionmentioning
confidence: 98%